Development of Task Deployment Tool for Operating IoT Devices - Hang, Lei; Kim, Do-Hyeun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Business processes utilize IoT data to interact with the data in physical world, to make informed decisions, improve their execution, and adjust to set context changes.Methods/Statistical analysis: A novel IoT task deployment tool is proposed in this paper for efficiently executing and allocating the business process model to real IoT devices. The designed tool can extract the operational sequence from the task editor and interact directly with remote IoT devices to perform defined tasks.Findings:An application in a mobile device is implemented to validate the feasibility of the proposed approach, in which CoAP protocol is used for the communication. The results show that the proposed task deployment tool can retrieve and parse tasks efficiently.Improvements/Applications: In future, we will conduct real experiment with more IoT devices to verify the proposed model for task deployment.Â Â
Keywords: Internet of Things; Business Process Modeling; Task Deployment; CoAP; Mobile.